1982
DOI: 10.1021/bi00536a017
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of neurophysin self-association and neuropeptide hormone binding as expressed by quantitative affinity chromatography

Abstract: The reciprocal modulation of neurophysin self-association and noncovalent peptide--protein interaction between neurophysin and the hormones oxytocin and vasopressin has been assessed by quantitative affinity chromatography. Competitive elutions of radiolabeled bovine neurophysin II (NPII) from the affinity matrices Met-Tyr-Phe-omega-(amino-hexyl)- [and (aminobutyl)-] agarose were performed with increasing concentrations of either of the soluble ligands oxytocin or lysine-vasopressin. Also, the dependence of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…The close agreement with literature values for the soluble protein (Whittaker and Allewell, 1984) shows that immobilization on the high performance affinity supports described above does not alter the self-association properties of neurophysin, at least statistically. In contrast, with Sepharose-bound neurophysin, a dimerization constant that is roughly 10-fold higher than in solution was obtained (Angal and Chaiken, 1982;Chaiken et a/., 1983). This result is unexpected since any disruption of the recognition surfaces that may occur on immobilization can be foreseen to decrease the association capacity of the insoluble material.…”
Section: Neuroph Ysinmentioning
confidence: 95%
See 1 more Smart Citation
“…The close agreement with literature values for the soluble protein (Whittaker and Allewell, 1984) shows that immobilization on the high performance affinity supports described above does not alter the self-association properties of neurophysin, at least statistically. In contrast, with Sepharose-bound neurophysin, a dimerization constant that is roughly 10-fold higher than in solution was obtained (Angal and Chaiken, 1982;Chaiken et a/., 1983). This result is unexpected since any disruption of the recognition surfaces that may occur on immobilization can be foreseen to decrease the association capacity of the insoluble material.…”
Section: Neuroph Ysinmentioning
confidence: 95%
“…Bovine neurophysin I1 has been immobilized on supports of a different nature, namely Sepharose 4B (Angal and Chaiken, 1982;Chaiken et al, 1983) and more recently on several pressure-resistant affinity supports, such as nonporous glass (NPG) beads , ACCELL (polyacrylamide-coated silica, from Waters) and highly cross linked (HXL) agarose (from LKB) (Fassina et al, 1986;Fassina and Chaiken, 1988), that are suitable for use with high performance liquid chromatographic instrumentation. To this end the immobilized protein was packed in an HPLC column and used as an analytical tool in an HPLC system.…”
Section: Neuroph Ysinmentioning
confidence: 99%
“…The preparation of affinity matrices used for this study has been described elsewhere (23). Bed volumes and immobilized polypeptide concentrations for these matrices were 2.5 ml and 0.30pmol peptide/ml of bed volume for Met-Tyr-Phe-AB-agarose and 2 ml and 0.…”
Section: Affinity Chromatographymentioning
confidence: 99%
“…Amino acid analysis of the final product indicated that the overall yield of [3-nitro-Tyr 491 BNP-I1 was approximately 30% of the starting NP-11. Native neurophysins and [3-nitro-Tyr 491 BNP-I1 were I-labeled by reacting at amino groups using Bolton-Hunter reagent (Nsuccinimidyl-3(4-hydroxy-5-[ I] iodophenyl) propionate) (23,38). After reaction the iodinated proteins were purified by Sephadex (3-25 chromatography in 0.4 M ammonium acetate, pH5.7, followed by affinity chromatography on Met-Tyr-Phe-AH-agarose (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation